Phenotypic differences in individuals with autism spectrum disorder born preterm and at term gestation. (August 2015) - Bowers, Katherine; Wink, Logan K; Pottenger, Amy; McDougle, Christopher J; Erickson, Craig
The objective of the study was to characterize the phenotype of males and females with autism spectrum disorder born preterm versus those born at term. Descriptive statistical analyses identified differences between male and female autism spectrum disorder subjects born preterm compared to term for several phenotypic characteristics and comorbidities. Of the 115 (13.0% of 883) born preterm, a greater percentage of males had sleep apnea (13.8% vs 2.5%, p < 0.0001), seizure disorders (17.0% vs 8.5%, p = 0.01), and attention-deficit/hyperactivity disorder (14.9% vs 6.6%, p = 0.005). Females born preterm were more likely to be nonverbal (22.2% vs 4.6%, p = 0.001). In summary, phenotypic differences were observed, especially among males. The results may have implications for understanding the underpinnings of a subset of individuals with autism spectrum disorder and contribute to the development of focused treatments for autism spectrum disorder among children born preterm.